2020
DOI: 10.1021/acs.orglett.0c02938
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacophore-Directed Retrosynthesis Applied to Ophiobolin A: Simplified Bicyclic Derivatives Displaying Anticancer Activity

Abstract: Pharmacophore-directed retrosynthesis applied to ophiobolin A led to bicyclic derivatives that were synthesized and display anticancer activity. Key features of the ultimate defensive synthetic strategy include a Michael addition/facially selective protonation sequence to set the critical C6 stereocenter and a ringclosing metathesis to form the cyclooctene. Cytotoxicity assays toward a breast cancer cell line (MDA-MB-231) confirm the anticipated importance of structural complexity for selectivity (vs MCF10A ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 63 publications
(98 reference statements)
0
16
0
Order By: Relevance
“…1,3,14 Guided by this model, Taube and Romo developed (±)-5, a fragment of 1 that emerged as the minimal substructure for activity against the triple-negative MDA-MB-231 breast cancer cell line. 15 However, this study revealed a significant difference in efficacy between (±)-5 and 1, suggesting an important ancillary role for the C and D rings. 16 This observation inspired us to explore a different approach to the 5−8−5 carbocyclic nucleus of 1.…”
mentioning
confidence: 51%
“…1,3,14 Guided by this model, Taube and Romo developed (±)-5, a fragment of 1 that emerged as the minimal substructure for activity against the triple-negative MDA-MB-231 breast cancer cell line. 15 However, this study revealed a significant difference in efficacy between (±)-5 and 1, suggesting an important ancillary role for the C and D rings. 16 This observation inspired us to explore a different approach to the 5−8−5 carbocyclic nucleus of 1.…”
mentioning
confidence: 51%
“…The same challenge was obvious in our synthesis as various conditions with different copper sources were unsuccessful in delivering the desired coupling product. Ultimately, lithium-halogen exchange followed by the treatment with (2-thienyl)­Cu­(CN)­Li transformed the alkyl iodide 5 into a reactive organocuprate that resulted in efficient conjugate addition with the assistance of TMSCl leading to the corresponding TMS-enol ether . The labile TMS group was then removed under acidic workup conditions to yield the cyclopentenone 30 in 96% yield.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Ultimately, lithium-halogen 20 followed by the treatment with 21 transformed the alkyl iodide 5 into a organocuprate that resulted in efficient conjugate with assistance of TMSCl leading the corresponding TMS-enol ether. 22 The TMS group then removed under acidic workup conditions to yield cyclopentenone 30 in 96% yield. The ketone group in 30 was converted to vinyl triflate 32 using Comins' reagent (31) in 69% yield.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…We have recently disclosed the completion of Stage I and initial Stage II studies 57 in which application of PDR enabled optimization of the A-ring synthesis involving a substratecontrolled conjugate addition and facially-selective protonation, key for installation of the critical C6-stereocenter. This one pot process enabled would ultimately enable annulation of the B and C rings, and closure of the 8-membered ring using Nakada's RCM strategy.…”
Section: Pdr Applied To Ophiobolin Amentioning
confidence: 99%
“…Thus, the knowledge gained through these studies was compiled to devise the synthesis of OpA bicyclic derivatives (Scheme 13) and is also proving extremely useful in informing the chemistry to synthesize both tricyclic derivatives and the natural product itself. 57 Beyond the extensive synthetic knowledge gleaned from the synthesis of the bicyclic derivative 74, we also obtained some interesting biological activity from the bicyclic derivatives of OpA. Given the ease of accessing the epimeric C3-des-methyl bicyclic derivative bearing a secondary alcohol, bicyclic derivative 85, this was also synthesized to provide information regarding the importance of the C3 alcohol stereochemistry.…”
Section: Pdr Applied To Ophiobolin Amentioning
confidence: 99%